Penile Dimensions of Newborn Infants - M. Suttan Assin; Jusuf Rukman; Adrizal Dahlan (Indonesian Pediatric Society, 1989)
Of 336 full-term, newborn male tnfanrs, penile diameter, length, and volume of the testis were measured. All of the infants were Indonesians. The penile stretched length was 2.86 Â± 0.23 cm and the diameter 0.82 Â± 0.33 cm. There was statitiscally a significant correlation between penile length and gestational age (P<0.01), but no significant correlation between penile length and testicular volume, body length, body weight, or head circumference.